(3GdQbGHI GdbVGFjI Ydi VeGfGJ GdMQjI GdTNUjI aj eQMdI GdGSJOdGd (B: s (3OQGSI ebGQfI (B/ s - (3eGgQ YHOGddg Ydj s; (3eMehO eMeO cHjT (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2010)
(3JYO eQMdI LeY GdGSJOdGdGJ ef Gge GdeQGMd GdJi JSHb GdOYhi GdLfGFjI hPdc HGdfXQ Gdi eGjJQJH YdjgG ef GLQGAGJ eJUdI HgG cGdGSJLhGH hGdMHS GdGMJjGWi hGdGMGdI hGdeMGceI aajgG jJe GdJMaX Ydi GdeTJHg ajg hajgG QNU GdbVGA GSJjbGag hGdJYQV dMQjJg ai GdJfbd hajgG GLGR GdeTQY GdJYQV GdeGOi hGdGbJjGO ef ZjQ eCehQi GdVHW GdbVGFi ai MGdGJ eYjfI HGdEVGaI Gdi LeY GdCOdI hGdbQGFf hGdOdGFd Mhd GdLQjeI hGLQGA GdJMQjGJ hSeGY GbhGd GdeTJHg ajg s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2010. s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMQjI GdTNUjI s; (3MQjI GdJfbds; (3MQeI GdMjGI GdNGUIs; (3CYeGd GdGSJOdGds; (3GdJMaXs; (3GdGSJjbGas; (3GdGYJbGds; (3GdGbJjGOs; (3VeGfGJ GdMQjI GdTNUjIs; (3GdbGfhf GdaQfSjs; (3GdbGfhf GdCeQjcjs; (3GdbGfhf GdEfLdjRjs; (3GdQbGHI GdbVGFjI Ydi bQGQGJ GdGYJbGds; (3GdQbGHI GdbVGFjI Ydi eTQhYjI CYeGd GdGSJOdGds; (3GdeSFhdjI GdLfGFjI Yf GdbHVs; (3GdeSFhdjI GdLfGFjI Yf CYeGd GdGSJOdGds; (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs -- 2010